Nutrient Cycle in Eucalyptus tereticornis Smith Plantations - Singh, R. P. (Indian Forester, 1984)
The present investigation deals with the nutrients cycle in five 10 nine years old Eucalyptus tereticornis Smith plantations. Different plants paris were analysed for nitrogen, phosphorus and calcium and results are given of the amount of these elements in the leaves, branches, boles and rools. Total amount of these elemenls on average tree basis is also determined. Amount of nutrient released through literfall is also eslimaled and comparalive account of annual uptake, retention and release of nutrients is prepared.